Acute and late vaginal toxicity after adjuvant high-dose-rate vaginal brachytherapy in patients with intermediate risk endometrial cancer: is local therapy with hyaluronic acid of clinical benefit? - Laliscia, Concetta; Delishaj, Durim; Fabrini, Maria Grazia; Gonnelli, Alessandra; Morganti, Riccardo; Perrone, Franco; Tana, Roberta; Paiar, Fabiola; Gadducci, Angiolo (Journal of Contemporary Brachytherapy, 2016)
Purpose : The aim of the present study was to evaluate the effectiveness of hyaluronic acid (HA) in the prevention of acute and late vaginal toxicities after high-dose-rate (HDR) vaginal brachytherapy (BT). Material and methods : Between January 2011 and January 2015, we retrospectively analyzed 126 patients with endometrial cancer who underwent extrafascial hysterectomy with or without lymphadenectomy and adjuvant HDR-vaginal BT +/– adjuvant chemotherapy. The total dose prescription was 21 Gy in 3 fractions (one fraction for week). Vaginal ovules containing 5 mg of HA were given for whole duration of vaginal BT and for the two following weeks. Acute and late toxicities were evaluated according to CTCAE vs 4.02. Results : According to the revised FIGO 2009 classification, most tumors were in stage IA (30.9%) and in stage IB (57.9%). Thirty-three patients (26.2%) received adjuvant chemotherapy before vaginal BT. Five-year disease-free survival (DFS) and five-year overall survival (OS) were 88% and 93%, respectively. The most common grade 1-2 acute toxicities were vaginal inflammation (18 patients, 14.3%) and dyspareunia (7 patients, 5.5%). Two patients (1.6%) had more than one toxicity. Late toxicity occurred in 20 patients (15.9%). Grade 1-2 late toxicities were fibrosis (14 patients, 11.1%) and telangiectasias (7 patients, 5.5%). Six patients (4.8%) had more than one late toxicity. No grade 3 or higher acute or late toxicities were observed. Conclusions : These results appear to suggest that the local therapy with HA is of clinical benefit for intermediate risk endometrial cancer patients who receive adjuvant HDR-vaginal BT after surgery. A randomized trial comparing HA treatment vs. no local treatment in this clinical setting is warranted to further evaluate the efficacy of HA in preventing vaginal BT-related vaginal toxicity.